MORFOLOGI KELENJAR ANAL MUSANG LUAK BETINA (PARADOXURUS HERMAPHRODITUS) - Inggrid Trinidad Maha; I Ketut Mudite Adnyane; Savitri Novelina (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2018)
The common palm civet (Paradoxurus hermaphroditus) is one of the mammalian in Indonesia which have anal gland in female and fefemale that located in the lower tail. This research was aimed to describe the morphology of anal gland of common palm civet female. One female of common palm civet was used in this research which observed macroscopic and microscopic.The result showed that common palm civet have a pair of anal gland which hasshaped like ball and located in the anal sacs wall’s in the ventrolateral of anus.Each anal gland has a ostium of anal canal dorsolaterally in the cutaneous zone of anal canal . Microscopic observation showed a well developed sebaceous gland and apocrine sweat gland in the wall of anal sac. Sebaceous and apocrine glands were excreted their product into main ductus to the anal canal.